Elaborasi Model Technology Acceptance Model (TAM) dan DeLone & McLean Untuk Mengukur Faktor Penggunaan ShopeePay - Romlah Novianti; Wira Bharata (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The use of digital wallets in Indonesia is increasing both by online shopping or shopping directly. There are various factors that behind the use of digital wallets by the Indonesian people. This study seek to find out the influence of the factors that are the background for using digital wallets which in this case is ShopeePay, by knowing the effect of Easy of Use to Intention to Use and User Satisfaction and impact it has on the Net Benefit. This study combined two forms of information system research model that is the Technology Acceptance Model (TAM) and the Delone and McLean model. This research is carried out with a quantitative approach through the asosiatif method using by the likert scale. The sampling technique used is nonprobability sampling, with a total sample is 100 respondents from ShopeePay user. The results of this research support all of hypotheses, showing that there are positive and significant effects of the Easy of Use to Intention to Use and User Satisfaction and their impact on the Net Benefits. The highest relationship rate is in the Easy of Use variable to Intention to Use variable with a original value of samples by 0.696 or 69%.